Tratamiento homeopático de la cefalea tensional con Nux vómica: reporte de un caso (2021)
Tension headache is a highly prevalent pathology, which has impacts not only on the physical health of people, also on the work and social level. Considering the above, from Complementary Medicines there are different therapeutic tools, including Homeopathy. The present work describes the report of a successful case of a tension headache box managed homeopathically with the drug Nux vomica in the Student Health Care Center (CASE), within the Alternative Medicine consultation of the National University of Colombia- Headquarters Bogotá, during the years 2018-2019.